2015
DOI: 10.1038/mt.2015.128
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin Haplotypes Provide Prioritized Target Panels for Allele-specific Silencing in Huntington Disease Patients of European Ancestry

Abstract: Huntington disease (HD) is a dominant neurodegenerative disorder caused by a CAG repeat expansion in the Huntingtin gene (HTT). Heterozygous polymorphisms in cis with the mutation allow for allele-specific suppression of the pathogenic HTT transcript as a therapeutic strategy. To prioritize target selection, precise heterozygosity estimates are needed across diverse HD patient populations. Here we present the first comprehensive investigation of all common target alleles across the HTT gene, using 738 referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
98
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 41 publications
3
98
0
1
Order By: Relevance
“…Some SNPs (single nucleotide polymorphisms) were reported as factors that could interfere in genetic stability of the CAG polymorphic region (HTT). It is believed that a specific SNP profile can determine the degree of predisposition in the event of CAG expansion at the HTT gene (Warby et al, 2009;Kay et al, 2015). Different SNP haplogroups have been built in order to categorize individuals with normal CAG alleles and expanded ones in different ancestral origin populations (Warby et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some SNPs (single nucleotide polymorphisms) were reported as factors that could interfere in genetic stability of the CAG polymorphic region (HTT). It is believed that a specific SNP profile can determine the degree of predisposition in the event of CAG expansion at the HTT gene (Warby et al, 2009;Kay et al, 2015). Different SNP haplogroups have been built in order to categorize individuals with normal CAG alleles and expanded ones in different ancestral origin populations (Warby et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to each genetic profile, these subjects are classified in haplogroups A, B, or C. In a sample of the European population, as known as of a high HD prevalence, it was observed that the haplogroup A is found in 95% of the affected individuals and, interestingly, the haplogroup A is also present in 53% of chromosomes of the general population (<27 CAG) (Warby et al, 2009). The haplogroups B and C have been found in populations that had low HD prevalence (Warby et al, 2009;Kay et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In populations of European ancestry where prevalence is highest, the expanded CAG repeat occurs preferentially on haplotypes A1, A2, and A3a, whereas in African and East Asian patients the HD mutation occurs on a heterogeneous mix of local haplotypes. [6][7][8][9] European HD haplotypes A1 and A2 do not occur in African and East Asian populations, suggesting that these haplotypes may account in part for higher HD prevalence rates in populations of European ancestry. 4,7 HD has been reported in many countries of Latin America, but detailed genetic investigations are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] European HD haplotypes A1 and A2 do not occur in African and East Asian populations, suggesting that these haplotypes may account in part for higher HD prevalence rates in populations of European ancestry. 4,7 HD has been reported in many countries of Latin America, but detailed genetic investigations are lacking. 10 Early clinical descriptions were reported in Cuba and Brazil, and subsequently in Argentina, Mexico, Peru, Chile, and Colombia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation